Small molecules antileishmanials: A review - Kulshrestha A.; Dhanawat M.; Das N.; Shrivastava S.K. (My University, 2025)
Leishmaniasis is caused by protozoan parasites belonging to the genus Leishmania. According to WHO, leishmaniasis occurs in four continents and is considered to be endemic in 88 countries, 72 of which are developing countries. Intensive effort to investigate novel compounds to counter the parasites that are resistant to existing drug molecules is necessary. This review intends to give an outline of the present state of knowledge on antileishmanial drugs along with molecules that are currently under development as promising drug candidate. A brief discussion on some aspects of associated drug resistance is also considered. © 2012 Bentham Science Publishers.